The Evolution of Lighting in South-West India from Night-Time Lights: 2012–2020 - Satheendran, S. Sumith; Chandran, S. Smitha; Mathew, John C. (Spatial information research (Online), 2022)
Human-induced alterations of the landscape and the same driven climate changes are seriously making drastic changes in the processes on the Earth's surface, regionally and globally. Visible Infrared Imaging Radiometer Suite (VIIRS) night-time light datasets can precisely detect the intensity and scope of human activities. Accurate and temporal monitoring of urban areas and urban sprawls is highly imperative to the detection and assessment of regional development of a region. This study quantitatively assessed and mapped the light extents and urban region in Kerala, one of the southwest Indian states from 2012 to 2020 with the help of low light imaging day/night band data collected from the VIIRS and utilised VIIRS night time Lights V.2 time series from the monthly averages with filtering to eliminate extraneous features such as aurora, biomass burning, and background. ISOCLUSTER based classification and the threshold methods are used for the light extent and urban region extraction respectively. The result indicated that the Kerala State experienced very high urbanization from 2012 to 2019. But in the case of 2020, there was a decrement in the radiance due to the lockdown and night curfews followed by the COVID-19 global pandemic. Normal life including transportation, industries, and business, etc. was affected much before the national lockdown in Kerala. It was proved with the help of time series data generated from mid-2019 to the end of 2020. The time-series data was generated with 580 night light datasets of NASA’s Black Marble VNP46A2 from 1st June 2019 to 31st December 2020 on daily basis. Graphical abstract